Prediction for Risk of Recurrence and Delayed Metastases of 1-16 Nasopharyngeal Carcinoma: An evaluation of CT scan - Phuprasat, Umasan; Churojana, Anchalee; Thepmongkol, Kullathorn (The ASEAN Journal of Radiology, 2013)
Purpose: To analyze the imaging characteristic on CT scan of the primary nasopharyngeal carcinoma which predict the locoregional recurrence. Materials and Methods: A retrospective review of 464 patients who had nasopharyngeal carcinoma at Siriraj Hospital, during 2004-2009 was performed. The treatment options were radiation therapy and concurrent chemotherapy corresponding to the staging, which were assessed by using CT. The patients who had no available initial imaging studies, incomplete treatment or had follow up less than 1 year were excluded. The imaging studies were analyzed for primary tumor size, direct tumor extension, and cervical lymph node involvement. The vascular invasion was defined as the obliteration more than half of the circumferential fat surrounding internal carotid artery. The regional nodes were evaluated for the levels of involvement and size of the largest one. Results: There were 99 patients (68 male, 31 female, mean age at 50 years) with the TNM classifications as follows: T15.2%, T2 39.4%, T3 24.2%, T4 21.2%, N0 18.2%, N1 14.1%, N2 46.5% and metastasis 11.76%. The extensions were prevertebral space (54.5%), masticator space (30.3%), skull base destruction (18.2%), and vascular invasion (42.4%). Nodal involvement was found in 81.8%. The most frequency of the largest lymph node was at ipsilateral level V (38.4%) and II (41.4%). Recurrence was found in 40.4% with averaged at 24 months after complete treatment (95%CI). Vascular invasion and skull base invasion had significant associated to predictive the risk of recurrence (P=0.04 and <0.001, respectively). The size of the tumor or lymph node showed no relation to the local regional recurrence or metastasis. Conclusion: The risks of NPC recurrence have been correlated to TNM staging, skull base, and carotid space involvement. Skull base invasion has been identified to be the predictive sign for tumor recurrence. Skull base invasion and carotid space involvement have also a statistically significant prognostic factor for overall survival.